(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND Cholecalciferol (vitamin D3) is widely supplemented in breast cancer survivors because of the role of vitamin D in multiple health outcomes. METHODS We conducted an observational study in 332 women in Eastern Switzerland with early, i.e., nonmetastatic breast cancer. Tumour-, patient-related and sociodemographic variables were recorded. Cholecalciferol intake and serum 25-hydroxyvitamin D (25(OH)D) and 1,25-dihydroxyvitamin D (1,25(OH)2D) levels were measured at the first visit (baseline) and during a follow-up visit in a median of 210 days (range 87–857) after the first visit. Patients presenting 25(OH)D deficiency were advised to take cholecalciferol supplementation. RESULTS At baseline, 60 (18%) patients had 25(OH)D deficiency (≤50 nmol/l, ≤20 ng/l), and 70 (21%) had insufficiency (50–74 nmol/l, 20–29 ng/l). Out of 121 patients with ongoing cholecalciferol supplementation at baseline, 25(OH)D deficiency and insufficiency was observed in 9 (7%) and 16 (13%) patients, respectively, whereas out of 52 patients with no supplementation, 15 (29%) had deficiency and 19 (37%) had insufficiency. Only 85 (26%) patients had optimal 25(OH)D levels (75–100 nmol/l, 30–40 ng/l) at baseline. Seasonal variation was significant for 25(OH)D (p = 0.042) and 1,25(OH)2D (p = 0.001) levels. Living in a rural area was associated with a higher median 25(OH)D concentration as compared with living in an urban area (87 nmol/l, range 16–216 vs 72 nmol/l, range 17–162; p = 0.001). Regular sporting activity was positively associated with 25(OH)D (p = 0.045). Body mass index was inversely related to both 25(OH)D and 1,25(OH)2D (Spearman’s rho = −0.24, p <0.001; rho = −0.23, p <0.001, respectively). The levels of 25(OH)D and 1,25(OH)2D were correlated (rho = 0.21, p <0.001). Age and bone mineral density had no significant correlation with the levels of 25(OH)D. Follow-up 25(OH)D was available for 230 patients, 44 (19%) of whom had 25(OH)D deficiency and 47 (21%) had insufficiency; 25 (41.6%) initially 25(OH)D-deficient patients attained sufficient 25(OH)D levels, whereas 33 (16.5%) patients with sufficient baseline 25(OH)D levels became deficient. Only 67 (30%) patients presented optimal 25(OH)D at the follow-up. CONCLUSION A remarkable fraction of the patients had serum 25(OH)D below (40%) or above (30%) optimal levels, and only around 30% of patients had optimal levels. Levels of 25(OH)D and 1,25(OH)2D increased on cholecalciferol supplementation, but the usual supplementation regimens were not adequate to bring 25(OH)D to the optimal range for a large proportion of patients. Trial registration number EKSG 08/082/2B.